2020
DOI: 10.1093/hropen/hoaa001
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interobserver reproducibility of pelvic ultrasound for the detection and measurement of endometriotic lesions

Abstract: STUDY QUESTION What is the interobserver and intraobserver reproducibility of pelvic ultrasound for the detection of endometriotic lesions? SUMMARY ANSWER Pelvic ultrasound is highly reproducible for the detection of pelvic endometriotic lesions. WHAT IS KNOWN ALREADY Transvaginal ultrasound (TVS) has been widely adopted as the first-line assessment for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
3
29
0
1
Order By: Relevance
“…The few studies about reproducibility present in the literature are related to expert operators (usually no more than 2) of the same center. [8][9][10] To the best of our knowledge, no study has reported if less expert operators can accurately replicate the results of experts. The aim of the present multicenter study was to evaluate the reproducibility of ultrasonographic (US) findings of rectosigmoid endometriosis among examiners with different level of expertise in different centers using stored 3D volumes of the posterior compartment of the pelvis as a part of SANABA (Sardinia-Navarra-Barcelona) collaborative study.…”
mentioning
confidence: 99%
“…The few studies about reproducibility present in the literature are related to expert operators (usually no more than 2) of the same center. [8][9][10] To the best of our knowledge, no study has reported if less expert operators can accurately replicate the results of experts. The aim of the present multicenter study was to evaluate the reproducibility of ultrasonographic (US) findings of rectosigmoid endometriosis among examiners with different level of expertise in different centers using stored 3D volumes of the posterior compartment of the pelvis as a part of SANABA (Sardinia-Navarra-Barcelona) collaborative study.…”
mentioning
confidence: 99%
“…However, the IDEA consensus was not used. Contrarily, Bean et al 36 recently reported good interobserver variability (ICC, 0.88 (95% CI, 0.72-0.95)) and excellent intraobserver variability (ICC, 0.93 (95% CI, 0.82-0.97) and ICC, 0.96 (95% CI, 0.90-0.98)) of bowel lesion measurements on TVS. In a single-center study, Di Giovanni et al 20 found no statistically significant difference in the measurements of any of the three dimensions of rectosigmoid DE lesions when comparing TVS and PSM.…”
Section: Discussionmentioning
confidence: 93%
“…The accuracy of ultrasound for the diagnosis of pelvic endometriosis has greatly improved over recent years, and it is widely regarded as the first-line diagnostic tool, despite a significant interobserver variability has been reported [ 68 ]. Certainly, the identification of extra-genitalia lesions requires a specific training [ 69 ]; however, ongoing practice is necessary to acquire and maintain competence [ 70 ].…”
Section: Discussionmentioning
confidence: 99%